Pengaruh Pengetahuan Produk, Inklusi Keuangan Syariah, Lingkungan Sosial, dan Disposable Income Terhadap Keputusan Menabung di Bank Syariah Dengan Religiusitas Sebagai Variabel Moderating - Rahayu, Nadi Harvita; Hakim, Luqman (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
The aim of this research is to determine the impact of product knowledge, sharia financial inclusion, social environment, as well as disposable income on the decision to save at a sharia bank with the moderating variable religiosity. This type of research is quantitative research with data collection techniques using questionnaires. The population in the study were customers of Bank Syariah Indonesia (BSI) KCP Surabaya Wiyung who had savings accounts and the sampling technique used accidental sampling. The data analysis technique uses SEM PLS analysis with the help of WarpPLS 8.0 software. The results of this research include product knowledge, sharia financial inclusion, and disposable income has a positive and significant influence on the decision to save at a sharia bank, but the social environment does not significantly influence the decision to save at a sharia bank. Religiosity is able to moderate the influence of sharia financial inclusion on the decision to save at sharia banks. However, religiosity cannot moderate the influence of product knowledge, social environment, and disposable income on the decision to save at a sharia bank.